Local WisdomandBuddhist Beliefs - Leksri, Phra Saengchan (Journal of Graduate Saket Review, 2020)
This article is intended to present local wisdom and Buddhist beliefs. The local wisdom about faith occurs from thinking that this thing is good that is not good or must affects that faith. Therefore appears to be a taboo of ancient teachings, local wisdom which is knowledge that has the characteristics of accumulating, learning, inheriting and continuing from the past to the present, from the ancestors to the long-standing generations together, and is related and consistent with the traditional way of life of villagers without separation. The belief in Buddhism teaches belief on the basis of reason, belief, karma or action. Believing the result of every action will occur appropriately according to the cause and practice in various matters by training the mind to gain access to wisdom, to provide complete physical and mental health. Local wisdom and Buddhist beliefs assumed that when Buddhism spread its influence in that region, the teachings of the Buddha that are hidden in the local wisdom about faith should begin and combine with local wisdom and traditional beliefs that existed before. This should be consistent with the principles of Buddhism and merge harmoniously and then become a culture, tradition and tradition for people in the society to behave together until today.